Rural exodus and standard of living: Raising the standard of living and the productivity of Mongolian nomadic households - Friedrich Thießen; Thomas Maurer; Altangerel Lkhamsuren (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2019)
As in many other countries of the world there is migration in Mongolia. The quality of life in cities is developing rapidly, while progress in the countryside is only slight. A research project by GMIT and TUC is investigating the causes of rural exodus and ways to prevent it or slow it down. In a first phase, an inventory of the income situation and living standards of nomadic households was carried out. It is based on an intensive qualitative and quantitative survey of nomadic households in different spatial and socio-economic life situations. The results show that the nomadic households' income is too low to make the purchases of typical consumer durables that are common in urban regions. Almost all nomads have telephones, television, solar collectors and light. Motorcycles, a car and/or a truck are much less common. Other durable consumer goods, owned by 74 % of urban households, are possessed by only 10 % of the nomads. Nomads wish for better sanitary facilities like toilets, showers or running water supply. They also desire improved living conditions with separate living and sleeping areas, windows, wardrobes and a simpler heating. Nomads also long for equipment to make work easier, such as washing machines, gas or electric cookers or refrigerators and freezers, which only account for 31 % of nomads, compared to 84 % in urban households. All appliances should be robust and suitable for relocation. Overall, the study shows that the migration of nomads from the steppes to the cities can be explained by a change in lifestyle in order to achieve a higher standard of living.
Keywords: 330